2011
DOI: 10.1148/radiol.11101939
|View full text |Cite
|
Sign up to set email alerts
|

Rising Use of CT in Child Visits to the Emergency Department in the United States, 1995–2008

Abstract: Use of CT in children who visit the ED has increased substantially and occurs primarily at non-pediatric-focused facilities. This underscores the need for special attention to this vulnerable population to ensure that imaging is appropriately ordered, performed, and interpreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(137 citation statements)
references
References 36 publications
2
128
2
5
Order By: Relevance
“…Our results are similar to other studies examining use trends of various imaging modalities in EDs. 15,16 A NHAMCS study of use trends for computed tomography imaging in children seen in EDs found a fivefold increase from 1995 to 2008; 89.4% of the increased use took place at non-pediatric-focused facilities. 15 What accounts for our observations in the ED use of radiographs for asthma?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are similar to other studies examining use trends of various imaging modalities in EDs. 15,16 A NHAMCS study of use trends for computed tomography imaging in children seen in EDs found a fivefold increase from 1995 to 2008; 89.4% of the increased use took place at non-pediatric-focused facilities. 15 What accounts for our observations in the ED use of radiographs for asthma?…”
Section: Discussionmentioning
confidence: 99%
“…15,16 A NHAMCS study of use trends for computed tomography imaging in children seen in EDs found a fivefold increase from 1995 to 2008; 89.4% of the increased use took place at non-pediatric-focused facilities. 15 What accounts for our observations in the ED use of radiographs for asthma? A review of changes in the National Asthma Education and Prevention Program guidelines from 1991 onward did not account for the trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 TS-höfuð var algengasta rannsóknin á Landspítala (40,3%) en þó var hlutfall TS-rannsókna af höfði laegra þar en víða annars staðar. 13,15 Mikil notkun TS vegna höfuðáverka barna 20 hefur leitt til þess að gerðar hafa verið klínískar leiðbeiningar 21 meðal annars á íslensku, 22 sem án efa stuðla að viðeigandi notkun. Það er hins vegar viðurkennt vandamál í Evrópu að leiðbeiningar fyrir tilvísandi laekna vantar víða 15 og fáar leiðbeiningar um val myndrannsókna eru til á íslensku.…”
Section: Umraeðaunclassified
“…The percentage of emergency department visits for head trauma resulting in CT examinations rose steadily from 12% in 1997 to 34% in 2008. 2 Increased awareness of the potential long-term hazards of radiation, particularly in children, [3][4][5] has engaged physicians and regulators in attempts to decrease CT use without compromising patient care. 6,7 In August 2001, a multidisciplinary group, including 40 pediatric radiologists, gathered for the ALARA conference.…”
mentioning
confidence: 99%